Diplomasi Keluarga Dalam Islam - Moch. Azis Qoharuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Diplomations plays the most important role in a family. Due to family is the smallest unit in society, it influences the family members to have good values in communication to be implemented in society, later. Furthermore, Islam has its own perpective on communication. It guides the family to interact among the siblings and so forth. Islam shows the principles that should be obeyed to create comfort life.